Persistence of protective anti-HBs antibody levels and anamnestic response to HBV booster vaccination: A cross-sectional study among healthcare students 20 years following the universal immunization campaign in Italy - Guglielmo Dini; Alessandra Toletone; Ilaria Barberis; Nicoletta Debarbieri; Emanuela Massa; Chiara Paganino; Francesca Bersi; Alfredo Montecucco; Cristiano Alicino; Paolo Durando (Taylor & Francis Group, 2017)
Vaccination against Hepatitis B Virus (HBV) became mandatory in Italy for all newborns and 12 years-old individuals in the 1991. The immunogenicity of HBV vaccine and the effectiveness of the universal immunization strategy have been widely demonstrated. However the need to assess the antibody concentrations above the well known serological correlate of protection for HBV infection (≥10 mIU/mL), established in individuals immunized with a 3 doses vaccination course, is still recommended in subjects exposed to occupational risks in different settings, particularly the healthcare services. This practice has to be performed during the preventive medical examination, before the worker's exposure to biological hazards, as a fundamental part of Occupational Health Surveillance Programs in several Countries, including Italy: the goal is to assure individual protection, also providing booster doses when needed, after many years following the primary vaccination. During the 2011-2013 period, an observational study was performed in Healthcare students (HCSs) trained at a regional university acute-care hospital in North-Western Italy, properly immunized against HBV during infancy or adolescence, in order to evaluate the persistence of seroprotection and to assess the anamnestic response to booster vaccination. Data from 717 subjects undergoing HbsAg Ab and HBc Ab testing during the preventive medical examination, and receiving a booster dose of HBV vaccine when resulting with a non-protective titer (<10 mIU/mL), were collected and analyzed. Most of the HCSs (74.6%) included in the survey, mean age 24.8 y ( ± 4.6 SD), had received the primary vaccination course during the first year of life (3-5-11 months). Globally, 507 (70.7%) HCSs showed protective antibody titres, and an anamnestic response was observed in more than 95% subjects receiving the booster dose. Our study demonstrated the long-term persistence of protection of HBV vaccine, more than 20 y following the primary immunization, in HCSs who are exposed to occupational health risk. The anamnestic response observed in non-seroprotected subjects who received the booster further confirms the capability of the HBV vaccine to create a strong immunological memory.